(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This article explores modern methods of teaching English as a foreign language (EFL) to non-native speakers, focusing on approaches that emphasize communication, learner engagement, and contextual language use. It highlights the shift away from traditional grammar-translation methods toward communicative and task-based approaches such as Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), Blended Learning, and Project-Based Learning (PBL).